Energy efficiency and the link with society - Anchundia, Maria José López; Gámez, María Rodríguez; Quiroz, Alcira Magdalena Vélez; Miles, Gino Mieles; Molina, Lucio Alfredo Valarezo (International research journal of management, IT and social sciences, 2022)
The results obtained in the linking process are shown with society as one of the substantive activities, in the period 2021-2022 carried out by students of the Electrical Engineering career. The project encouraged students to train a group of people through practical methodologies to have minimum knowledge related to energy efficiency and renewable energy sources. The qualitative and quantitative method was used, which allowed describing the results of the survey without altering their respective variables. The population was made up of 45 people belonging to various cantons of the province of Manabí, such as Flavio Alfaro, Bahía de Caráquez, el Carmen, 24 de Mayo, Chone, Santa Ana, Rocafuerte and different places in the canton of Portoviejo, and province of Orellana, which were selected at random, the preparation of the didactic material was carried out. Among the results, it was highlighted that the participants did not know how energy can help the environment, but nevertheless they were aware that energy is related to the environment and dependence on society.